Implementation of Skinner's Behavioristic Learning Theory in Mathematics Learning in Increasing the Learning Interest of Grade 4 Elementary School Students - Anak Agung Istri Ari Krisna; Ni Ketut Suarni; I Gede Margunayasa (Psikostudia : Jurnal Psikologi, 2025)
This study aims to evaluate the effectiveness of the implementation of Skinner's Behavioristic Learning Theory in increasing the interest in learning mathematics of grade 4 elementary school students. The study sample involved 27 students, and data analysis was conducted focusing on changes in students' learning interest after the intervention. Sample characteristics, implementation of behavioristic theory, and data on student learning interest before and after the intervention were analyzed descriptively. Inferential statistical tests, such as t-tests, are used to determine the significance of changes in learning interest. The results showed an increase in students' interest in learning after the application of Skinner's Behavioristic Learning Theory, with relevant standard deviation values. The conclusion of this study provides an in-depth understanding of the positive impact of Skinner's Behavioristic Learning Theory in increasing interest in learning mathematics at the elementary level, with important implications for the development of effective learning strategies. Penelitian ini bertujuan untuk mengevaluasi efektivitas implementasi teori belajar behavioristik skinner dalam meningkatkan minat belajar matematika siswa kelas 4 SD. Sampel penelitian melibatkan 27 siswa, dan analisis data dilakukan dengan fokus pada perubahan minat belajar siswa setelah intervensi. Karakteristik sampel, implementasi teori behavioristik, dan data minat belajar siswa sebelum dan sesudah intervensi dianalisis secara deskriptif. Uji statistik inferensial, seperti uji-t, digunakan untuk menentukan signifikansi perubahan minat belajar. Hasil penelitian menunjukkan peningkatan signifikan dalam minat belajar siswa setelah penerapan Teori Belajar Behavioristik Skinner. Uji t berpasangan menghasilkan nilai t = [nilai t], p = [nilai p] < 0,05, yang mengindikasikan perbedaan signifikan antara pre-test dan post-test. Temuan ini menegaskan bahwa penguatan positif dalam pembelajaran dapat meningkatkan keterlibatan siswa, menciptakan lingkungan belajar yang lebih interaktif, serta menjadi landasan bagi pengembangan strategi pembelajaran matematika yang lebih efektif di tingkat sekolah dasar.